Effectiveness of the Demonstration Method in Improving Knowledge of Handling Work Accidents in the Parit Keladi I Village Community - Sutrisno, Sutrisno; Masdah, Siti; Wahyuni, Tri; Almumtahanah, Almumtahanah (International Journal of Health Sciences, 2025)
Workplace accidents pose a serious risk, especially in rural areas where formal occupational safety training is limited or nonexistent. This study investigates the effectiveness of the demonstration method in improving community knowledge and preparedness in handling work related injuries in Parit Keladi I Village. Using a qualitative participatory action research design, the study involved seven informants selected purposively, including farmers, community leaders, and health workers. Data collection methods included in depth interviews, participant observation, and documentation. Prior to the intervention, most participants relied on traditional or instinctive methods to treat injuries, often resulting in improper or delayed care. The introduction of demonstration based training significantly improved their understanding of proper first aid techniques, including wound cleaning, bandaging, and the use of antiseptics. Participants reported increased confidence and readiness to respond to accidents. The training was well received, with strong community engagement and support from local leadership, highlighting the potential for sustainability. The study concludes that the demonstration method is an effective, culturally sensitive approach to safety education in rural settings. It bridges the gap between knowledge and practice and fosters a proactive attitude toward accident prevention. Future efforts should include regular refresher sessions and leadership empowerment to strengthen the culture of safety within the community.